Language development an introduction - Owens, Robert E. (The Allyn & Bacon communication sciences and disorders series, 2012)
"As the most widely used text for introductory language development courses across the country, this comprehensive text allows students to understand every aspect of the discipline from a developmental perspective. Structured practically and chronologically, this text presents information in a highly readable manner for students. From language variations among children, new advances in linguistics and neurology, to the importance of literacy, the revised edition of Language Development: An Introduction includes expanded information regarding language development theories, bilingual and dialectical issues, and a unique emphasis on the constructionist perspective."--Back cover.